The geochemistry of minor elements in Pernambuco soils. I. Manganese in the Zona da Mata and Sertão - Horowitz, Arão; Dantas, Humberto da Silveira (Pesquisa Agropecuaria Brasileira, 2024)
Information on soil microelements of Brazil are scanty; and non-existent, as far as it is known, for North-East Brazil. The present work marks the beginning of the first systematic study of microelements in the typical soils of this region. Twelve profiles of typical soils of the interior (Sertão, aprox. 65.000km2 ) and 19 typical soil profiles of the region near the coast (Zona da Mata, aprox. 12.000km2) of the State of Pernambuco are studied. These profiles represent the major soil types of the region involved. In these soils, spectophotometer determinations were made on the Mn extracted by various agents sulfuric acid (Inst. Quim. Agrícola 1959), hydrofluoric acid, amonium acetate (pH═7), acetie acid 2,5%, (pH═2.5), and alcoolic hidroquinone 0.05% in order to study the geochemistry of manganese, and the amount available for the plants. In the soils of the semi-arid region of State of Pernambuco (Sertão), with the exception of some soils of the area shown in Fig. 1, the content of available manganese (easily reducible manganese) is considered sufficient to support plant life. The chances of manganese deficiency or toxicity, in these soils, is remote. In the soils near the coast (Zona da Mata) which are the most important from the agricultural point of view, the available Mn content is surprisingly low. The available Mn content for most of the soils is much lower than 20 ppm. It this content of easily reducible manganese (Jones & Leeper 1951) is to be accepted as the limit for a soil to be considered deficient in available manganese, most of the better soils of Pernambuco appear to be Mn deficient. Only one exception was found, for the soils of a narrow zone in the north of the Pernambuco State (Fig. 1), where available Mn content is enough to support the normal growth of plants. In this region, the chances of manganese deficiency or toxicity are also remote. It is perhaps possible to attribute, at least in part, to Ma and other minor elements deficiencies, the observed low yields of crops in the "Zona da Mata" even when these soils are irrigated and fertilized with macroelements. A deficiency of Co, Mo, and Zn, is also to be expected, as these elements are known to be associated (along with As, Ba, Ni and V) with Mn in sedimentary rocks. lt is emphasized the need of further investigations to prove in the field the statements made above, and to determine wether some endemic diseases in animals in that region, may be attributed to minor elements deficiencies. The geochemistry of Mn was not totally elucidated. The sulfuric acid method utilised (Inst. Quim. Agrícola 1959) failed to extract the total Mn in the soils. So, it was not possible to find any correlation between the total Mn content and the silt+clay portion, or the pH of the soils, even in the same profile. The hydrofluoric acid attack is more promising, and active work is now being conducted in the Soil Section of Instituto de Pesquisas e Experimentação Agropecuárias do Nordeste (IPEANE), in order to provide knowledge of the geochemistry of Mn in our soils. Even though field experiments have not been conducted by IPEANE staff members, the statements made above, are supported by the fact that in the narrow zone of Pernambuco State, were Mn is not deficient, better yields and better response to common fertilization (macroelements) were observed by a few scientists. The areas in which Mn deficiency is expected, are shown in Fig. 1.